Affective modulation of anterior cingulate cortex in young people at increased familial risk of depression. - Mannie, Z; Norbury, R; Murphy, SE; Inkster, B; Harmer, C; Cowen, P (2008)
BACKGROUND: We previously found that children of parents with depression showed impaired performance on a task of emotional categorisation. AIMS: To test the hypothesis that children of parents with depression would show abnormal neural responses in the anterior cingulate cortex, a brain region involved in the integration of emotional and cognitive information. METHOD: Eighteen young people (mean age 19.8 years) with no personal history of depression but with a biological parent with a history of major depression (FH+ participants) and 16 controls (mean age 19.9 years) underwent functional magnetic resonance imaging while completing an emotional counting Stroop task. RESULTS: Controls showed significant activation in the pregenual anterior cingulate cortex to both positive and negative words during the emotional Stroop task. This activation was absent in FH+ participants. CONCLUSIONS: Our findings show that people at increased familial risk of depression demonstrate impaired modulation of the anterior cingulate cortex in response to emotionally valenced stimuli.